THE RHETORIC IN CORPORATE SOCIAL RESPONSIBILITY (CSR) REPORTING : A FRAME ANALYSIS ON SUSTAINABILITY REPORTING OF PT. INDOSAT Tbk. - Rahmawati, Elok (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
The increasing of environmental consciousness is followed by the increasing of Sustainability Reporting disclosures which is used by company for reporting Corporate Social Responsibility (CSR) activities. Unfortunately, as profit oriented organizations, many companies have special aims while doing CSR programs, such as for avoiding tax, for violating laws, or sometimes for enhancing corporate reputation only. It can be seen that in Indonesia, the increasing of Sustainability Reporting disclosures does not followed by the environmental preservation. As a big company, ofcourse Indosat needs to report their activities, especially their CSR activities through the Sustainability Reporting. The successfulness of Indosat’s Sustainability Reporting is undeniable because they got many awards from this reporting. According to Luks (1998), actually everyone who produces sentences (written or oral), employs rhetoric. Therefore, this research intended to find what is the motivation of Indosat to disclose Sustainability Reporting. Frame analysis is used to analyzing the rhetorical data. Primary data sources are Indosat’s Sustainability Reporting 2009, 2010 and Indosat’s Annual Report 2011. Then, it is compared with the theories, news, and previous researches to find the truth. The implementation of Indosat’s CSR programs have a good assesment from their stakeholders. Based on the constitution, Indosat have not yet proven to be involved in law violation. Likewise in tax avoidance cases. However, it seems that corporation is always reduce expense, and tax is a great expense. Moreover, the profit which is allocated for CSR programs as much as approximately 1% up to 2% seems too small, although there is no certain standard which is stated by the constitution. Keywords : Rhetoric, Frame, Corporate Social Responsibility, Sustainability Reporting, Indosat